The Effect of Brain Gym as a Cognitive Stimulation Strategy in Improving Learning Concentration among School Aged Children - Assiella Dwi Putri; Retno Anggraeni Puspita Sari; Beatrix Elizabeth; Cicilia Nony Ayuningsih Bratajaya (Journal La Medihealtico, 2026)
School-age children are at the concrete operational development stage which requires good concentration skills in the learning process. However, the results of a preliminary study at SDIT Al-Kamiliyyah Bekasi Regency showed that many students still experience low concentration levels. Brain Gym is a non-pharmacological intervention in the form of a series of simple movements aimed at optimizing brain function and helping improve children's learning concentration. This study aims to determine the effect of the Brain Gym method on the level of learning concentration in school-age children at SDIT Al-Kamiliyyah Bekasi Regency. This study is a quantitative method with a pre-experimental design through a one group pretest - posttest approach. The study population was all 150 students in grades I and V, with a sample of 110 students selected using a purposive sampling technique. The concentration level was measured using the Grid Concentration Test (GCT). The Brain Gym intervention was given for two weeks with a frequency of three times a week. Data were analyzed using the Wilcoxon Signed Rank Test. Results: The analysis results showed a p-value <0.05, which means there is an effect of the Brain Gym method on increasing the level of learning concentration. Conclusion: The Brain Gym method is effective in increasing learning concentration in school-age children and is recommended as a non-pharmacological nursing therapy.